Aproximación de los estudiantes de grado décimo de la Institución Educativa Integral de Formación e Investigación Misak a la modelación matemática de situaciones reales a partir de las funciones cuadráticas (2020)
This research consisted of designing a strategy based on the development of a mathematical structure to approach the tenth grade students of the Misak comprehensive educational and research educational institution to the mathematical modeling of real situations using quadratic functions. The research was carried out in the following way. First, the mathematical structure of real numbers was studied, in which theory, mechanization, analysis, technological tools, and applications were articulated; the quadratic function was similarly studied. Then mathematical modeling processes were developed for two real situations, the first, consisted of finding a model that represented the free fall of an object, and the second, modeled the income for the sale of chickens in a poultry marketer in the municipality of Morales. Students took data, formulated and fitted quadratic mathematical models with the data obtained, and analyzed the information resulting from such models. Keywords: Mathematical modeling, real situations, quadratic functions, mathematical structure.